A reformed voice in the ecumenical discussion - Brinkman, M. E., 1950- (Studies in Reformed Theology, 2016)
In A Reformed Voice in the Ecumemenical Discussion Martien E. Brinkman offers a critical account of the main international ecumenical developments of the last three decades. He delivers a sketch of the Reformed contribution to the ecumenical dialogues dealing with issues like contextuality, state-church relations, the ethical implications of baptism, the church as sacrament of the kingdom and apostolic tradition. He pleas for a stronger non-Western input in the ecumenical discussions and emphasizes that in many contexts (Indonesia, India, China) the interreligious dialogue has become part of the inner-Christian dialogue. This study can be considered as a constructive contribution to the development of a hermeneutics of tradition and puts itself the critical question what is lost and found in translation.